Differential Regulation of Thyroid Hormone Metabolism Target Genes during Non-thyroidal Illness Syndrome Triggered by Fasting or Sepsis in Adult Mice - Fontes, Klaus N.; Cabanelas, Adriana; Bloise, Flavia F.; Andrade, Cherley Borba Vieira de; Souza, Luana L.; Wilieman, Marianna; Trevenzoli, Isis H.; Agra, Lais C.; Silva, Johnatas D.; Bandeira-Melo, Christianne; Silva, Pedro L.; Rocco, Patricia R. M.; et al. (Frontiers in Physiology, 2017)
Fasting and sepsis induce profound changes in thyroid hormone (TH) central and peripheral metabolism. These changes affect TH action and are called the nonthyroidal illness syndrome (NTIS). To date, it is still debated whether NTIS represents an adaptive response or a real hypothyroid state at the tissue level. Moreover, even though it has been considered the same syndrome, we hypothesized that fasting and sepsis induce a distinct set of changes in thyroid hormone metabolism. Herein, we aimed to evaluate the central and peripheral expression of genes involved in the transport (MCT8/Slc16a2 and MCT10/Slc16a10), metabolism (Dio1, Dio2 and Dio3) and action (Thra and Thrb) of TH during NTIS induced by fasting or sepsis. Male mice were subjected to a 48h period of fasting or cecal ligation and puncture (CLP)-induced sepsis. At the peripheral level, fasting led to: 1) reduced serum thyroxine (T4) and triiodothyronine (T3), expression of Dio1, Thra, Slc16a2 and MCT8 protein in liver; 2) increased hepatic Slc16a10 and Dio3 expression; and 3) decreased Slc16a2 and Slc16a10 expressions in the thyroid gland. Fasting resulted in reduction of Tshb expression in the pituitary and increased expression of Dio2 in total hypothalamus, arcuate (ARC) and paraventricular (PVN) nucleus. CLP induced sepsis resulted in reduced: 1) T4 serum levels; 2) Dio1, Slc16a2, Slc16a10, Thra and Thrb expression in liver as well as Slc16a2 expression in the thyroid gland 3) Thrb and Tshb mRNA expression in the pituitary; 4) total leukocyte counts in the bone marrow while increased its number in peritoneal and pleural fluids. In summary, fasting- or sepsis-driven NTIS promotes changes in the set point of hypothalamus-pituitary-thyroid axis through different mechanisms. Reduced hepatic THRs expression in conjunction with reduced TH transporters expression in the thyroid gland may indicate, respectively, reduction in the peripheral action and in the secretion of TH, which may contribute to the low TH serum levels observed in both models.